Task-Based Learning as an Effective Method in Teaching English Grammar - Jovliyeva Nafosat Bahodir qizi (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation: This article explores the effectiveness of Task-Based Learning (TBL) in teaching English grammar to EFL learners. Unlike traditional grammar instruction that focuses on explicit explanation and repetition, the task-based approach engages students in meaningful communication through problem-solving and real-life activities. The study highlights that when grammar is learned through authentic tasks, learners develop both grammatical accuracy and communicative fluency. The article also discusses how TBL promotes learner autonomy, motivation, and interaction, making grammar learning more practical and enjoyable.